2004
DOI: 10.1021/jm030207d
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 520. Isolation and Structure of Irciniastatins A and B from the Indo-Pacific Marine Sponge Ircinia ramosa

Abstract: The Indo-Pacific marine sponge Ircinia ramosa has been found to contain two powerful (GI50 from 0.001 to <0.0001 microg/mL) murine and human cancer cell growth inhibitors. Both were isolated (10(-3)-10(-4)% yields) by cancer cell line bioassay-guided techniques and named irciniastatins A (1) and B (2). Structural elucidation by a combination of spectral analyses, primarily high resolution mass and 2D-NMR (principally APT, HMQC, HMBC, and ROESY) spectroscopy, revealed the unusual structures 1 and 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
125
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 11 publications
10
125
1
3
Order By: Relevance
“…Intriguingly, metabolites with high structural similarity to pederin are also known from several different marine sponges (14). Many of these compounds exhibit extremely potent antitumor activity, and psymberin (15) [also known as irciniastatin A (16)] has recently been demonstrated to exhibit remarkably selective activity against solid tumor cell lines, which makes it a promising drug lead. The biological complexity of sponges can be enormous, because many species contain hundreds of distinct bacteria that can occupy up to 40% of their biomass (17).…”
mentioning
confidence: 99%
“…Intriguingly, metabolites with high structural similarity to pederin are also known from several different marine sponges (14). Many of these compounds exhibit extremely potent antitumor activity, and psymberin (15) [also known as irciniastatin A (16)] has recently been demonstrated to exhibit remarkably selective activity against solid tumor cell lines, which makes it a promising drug lead. The biological complexity of sponges can be enormous, because many species contain hundreds of distinct bacteria that can occupy up to 40% of their biomass (17).…”
mentioning
confidence: 99%
“…On the other hand they can be activated with suitable Lewis or Brønsted acids to generate reactive N-acylimines. In addition the N-acyl-N,O-acetal and the analogous N-acylhemiaminal motifs are found in a number of natural products with interesting biological activities, such as zampanolide (1), [2] psymberin (2), [3] or pederin (3) [4] ( Figure 1). Due to their importance several synthetic routes to Nacyl-N,O-acetals have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…and Ircinia ramose off the coast of Papua New Guinea by two independent research groups. [1,2] Its structural resemblance to other cytotoxins of the pederin family [e.g. pederin (2), mycalamide A (3) and the non-natural psympederin (4)], which are known to have strong antitumour properties, also suggested cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Its structural resemblance to other cytotoxins of the pederin family [e.g. pederin (2), mycalamide A (3) and the non-natural psympederin (4)], which are known to have strong antitumour properties, also suggested cytotoxic activity. Screening showed that psymberin (1) shows remarkable cytostatic activity against multiple human cancer cell lines with an LC 50 in nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%